Aktivitas Daya Ingat Ekstrak Daun Pecut Kuda (Stachtarpheta jamaicensis L. (Vahl) Pada Mencit Putih (Mus musculus) Dengan Metode Radial Arm Maze - Septiarini, Anita Dwi; Pratama, Kharisma Jayak; Andhika, Intan Fatna (Jurnal Farmasi & Sains Indonesia, 2024)
Alzheimer's disease is the most common type of dementia. Horse whip leaves contain flavonoid compounds which are widely used both in physiological aging studies and in rat model research, to research the cure of neurodegenerative diseases. The purpose of this study was to determine the activity of giving horse whip leaf extract and the effective dose of horse whip leaf extract in improving the memory power of mice. Horse whip leaf extract was extracted using 96% ethanol solvent by maceration method. Memory activity testing was carried out on male mice which were divided into 5 groups, namely the negative control group, the positive control group, the horse whip leaf extract test group at doses of 5, 10 and 20 mg/kg BW. The test was carried out using the radial arm maze method. The results showed that horse whip leaf extract had memory enhancing activity. Test animals that have been induced given treatment are known to experience a decrease in latency time which can be stated as test animals experience an increase in memory activity. The effective extract dose was a dose of 20 mg/kgBW with a difference in latency time of 49.80 second.